Élargir le cadre - Roger Odin (Mise au Point)
Based on the contributor’s personal experience, this article analyses the setting up of a cinema and audio-visual curriculum in French secondary schools and universities and deals with its implications: a temptation to focus on cinema as art with an aesthetical approach and an invitation to accept film as “myth”. The article advocates the necessity of openness in terms of objects (the whole field in which film language is used), approaches (all academic disciplines), methods (the development of technology making it possible to generalize a film practice) and pedagogical objectives (teaching art but also giving citizenship know-how and allowing self-development).